Implementing CAADP 2025 in Senegal: Identifying key sectors and policies promoting pro‐poor growth - Henning, Christian; Séne, Ligane Massamba; Hedtrich, Johannes; Fall, Cheickh Sadibou; Johnson, Michael E. (International Food Policy Research Institute, 2015)
The PEBAP project undertook in‐depth analyses of future economic growth and poverty reduction in three case‐study countries: Senegal, Ghana and Uganda. Analyses are based on a quantitative model we refer to as the CAADP‐lab tool‐kit. For each country researchers developed a baseline scenario of future economic growth and poverty reduction, projecting current CAADP‐2010 policies to 2025. Evidence on how spending and policy programs in agriculture and non‐agriculture in the past have helped transform each country’s economic growth and poverty reduction efforts was estimated using available national data. Results defined specific policy impact functions (PIFs) for each type of investment or policy reform in each individual country.